The Primary Chronicle in the Judean Chronograph (1262) - Vilkul, Tatiana (Український історичний журнал, 2025)
Recently, the time of the completion of the Judean Chronograph, which is the only definitely dated historical collection in Old Rus’ian literature, has been reconsidered based on a number of textual arguments. The purpose of this paper is to answer the question of whether the proposed revision is reasonable. It is also necessary to determine whether the compiler of the Chronograph was familiar with the Primary Chronicle since the dating of the Chronograph depends on the answer to this question. Textual criticism methods are applied here to address the problems of textual relationship. Scientific novelty. In the pages that follow, I offer a detailed analysis of quotations from the Primary Chronicle in the Judean Chronograph conducted for the first time. Conclusions. The author of the Chronograph knew the Chronicle well and quoted it both verbatim and in microcitations. The textual evidence does lead to the year 1262, so we have no reason to revise the traditional date of the compilation of the Chronograph.